Assessment of the various ionization methods in the analysis of metal salen complexes by mass spectrometry. (11th April 2014) - Słomińska, Beata; Chaładaj, Wojciech; Danikiewicz, Witold
<x xml:space="preserve">Abstract</x> Metal salen complexes are one of the most frequently used catalysts in enantioselective organic synthesis. In the present work, we compare a series of ionization methods that can be used for the mass spectral analysis of two types of metalosalens: ionic complexes (abbreviated as Com+X−) and neutral complexes (NCom). These methods include electron ionization and field desorption (FD) which can be applied to pure samples and atmospheric pressure ionization techniques: electrospray ionization (ESI), atmospheric pressure chemical ionization (APCI) and atmospheric pressure photoionization (APPI) which are suitable for solutions. We found that FD is a method of choice for recording molecular ions of the complexes containing even loosely bonded ligands. The results obtained using atmospheric pressure ionization methods show that the results depend mainly on the structure of metal salen complex and the ionization method. In ESI spectra, Com+ ions were observed, while in APCI and APPI spectra both Com+ and [Com + H]+ ions are observed in the ratio depending on the structure of the metal salen complex and the solvent used in the analysis. For complexes with tetrafluoroborate counterion, an elimination of BF3 took place, and ions corresponding to complexes with fluoride counterion were observed. Experiments comparing the relative sensitivity of ESI, APCI and APPI (with and without a dopant) methods showed that for the majority of the studied complexes ESI is the most sensitive one; however, the sensitivity of APCI is usually less than two times lower and for some compounds is even higher than the sensitivity of ESI. Both methods show very high linearity of the calibration curve in a range of about 3 orders of magnitude of the sample concentration. Copyright © 2014 John Wiley & Sons, Ltd.